The Transformation of Mother-Baby Bonding Attachment in Tufting Art - Abdillah, Afifah Ashma'; Wardoyo, Sugeng (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The bonding attachment between a mother and her baby is crucial and should be established as early as possible because it can significantly influence the baby’s psychological and social development. However, the public is often not fully aware of the long-term impact of this bond. The author transforms the concept of mother-baby bonding attachment into a tufting artwork, aiming to raise public awareness about its importance. This artwork not only highlights the significance of bonding attachment between mother and baby but also enriches the ideas and concepts of tufting art, providing the general public with a basic understanding of this vital connection. Tufting art is a technique used to create textile artworks by arranging and attaching threads to fabric with a specialized tufting tool, resulting in a rich, textured surface with tufted shapes. The method used is the practice-based research method or artistic research, consisting of literature research, drawing sketches, experiments, practices and possible outcomes. The outcome of this research is a tufting artwork that visually represents the bonding attachment between mother and baby. This artwork serves as both a reminder of the importance of the mother-child relationship and an effort to increase public awareness of the emotional bond’s vital role. There is still much room for further development in tufting art, especially with a broader approach. Future research could also explore combining tufting with other art media to create more diverse and impactful works.